Application of Learning Module Flipbooks With A STEAM Approach to Improve Scientific Attitudes and Collaboration Skills - Fuldiaratman, Fuldiaratman; Syahri, Wilda; Ekaputra, Firdiawan (PT Mattawang Mediatama Solution, 2024)
The purpose of this study was to apply the learning module flipbook with the STEAM approach in the philosophy of education course to improve students' scientific attitudes and collaboration skills. This study is experimental in nature and only uses one sample class. The subjects used in this study were Chemistry Education students at Jambi University who were taking chemical philosophy lectures. The utilization of the STEAM method in the learning module flipbook serves as the independent variable in this study, while the students' scientific mindset and teamwork abilities serve as the dependent variables. The data collection technique used in this study was a questionnaire to obtain information about students' scientific attitudes and collaboration skills. The results showed that the application of the learning module flipbook with the STEAM approach in the philosophy of education course was effective in improving students' scientific attitudes and collaboration skills with a significance value of 0.00.